Various steaming durations alter digestion, absorption, and fermentation by human gut microbiota outcomes of Polygonatum cyrtonema Hua polysaccharides - Wu, Weijing; Wang, Yanling; Yi, Ping; Su, Xufeng; Mi, Yan; Wu, Lanlan; Tan, Qianglai (Frontiers in Nutrition, 2024)
Introduction: Different steaming durations dramatically alter the structure of Polygonatum cyrtonema polysaccharides (PCPs). This study aimed to compare characteristics of digestion, absorption, and fermentation by gut microbiota across four representative PCPs from different steaming durations (0, 4, 8, and 12 hours), each with unique molecular weights and monosaccharide profiles. Methods: Chemical composition of the four PCPs was analyzed. Digestibility was evaluated using an in vitro saliva-gastrointestinal digestion model. Absorption characteristics were assessed with a Caco-2 monolayer model, and impacts on gut microbiota composition and short chain fatty acid (SCFA) levels were analyzed using in vitro fermentation with human gut microbiota. Results: Longer steaming durations altered the chemical profiles of PCPs, reducing carbohydrate content (84.87% to 49.58%) and increasing levels of uronic acid (13.99% to 19.61%), protein (1.07% to 5.43%), and polyphenols (0.05% to 2.75%). Four PCPs were unaffected by saliva digestion but showed enhanced gastrointestinal digestibility, with reducing sugar content rising from 4.06% (P0) to 38.5% (P12). The four PCPs showed varying absorption characteristics, with P0 having the highest permeability coefficient value of 9.59 × 10-8 cm/s. However, all PCPs exhibited poor permeability, favoring gut microbiota fermentation. The four PCPs altered gut microbiota composition and elevated SCFA production, but levels declined progressively with longer steaming durations. All PCPs significantly increased the abundance of Bacteroidota, Firmicutes, and Actinobacteriota, making them the dominant bacterial phyla. Additionally, all PCPs significantly increased the abundance of Bifidobacterium, Prevotella, and Faecalibacterium compared to the control group, which, along with Bacteroides, became the dominant microbiota. Increasing the steaming duration led to a reduction in Prevotella levels, with PCPs from raw rhizomes showing the highest relative abundance at 24.9%. PCPs from moderately steamed rhizomes (4h) led to a significant rise in Faecalibacterium (7.73%) among four PCPs. P8 and P12, derived from extensively steamed rhizomes (≥8 hours), exhibited similar gut microbiota compositions, with significantly higher relative abundances of Bacteroides (20.23-20.30%) and Bifidobacterium (21.05-21.51%) compared to P0 and P4. Discussion: This research highlights the importance of adjusting steaming durations to maximize the probiotic potential of P. cyrtonema polysaccharides, enhancing their effectiveness in modulating gut microbiota and SCFA levels.